2018
DOI: 10.1371/journal.pone.0202257
|View full text |Cite
|
Sign up to set email alerts
|

A pragmatic cluster randomised controlled trial of a tailored intervention to improve the initial management of suspected encephalitis

Abstract: ObjectiveTo determine whether a tailored multifaceted implementation strategy improves the initial management of patients with suspected encephalitis.DesignPragmatic two arm cluster randomised controlled trial.SettingHospitals within the United Kingdom.ParticipantsTwenty-four hospitals nested within 12 postgraduate deaneries. Patients were identified retrospectively by searching discharge, microbiology, radiology and pharmacy records and included if they met clinical criteria or had a recorded suspicion of enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Survivors of pediatric encephalitis demonstrate long-term neurological sequelae ranging from neurocognitive impairments and related learning challenges to behavioral and personality changes. 64 , 65 , 66 A 2016 meta-analysis found that a nearly half of the children who recover from viral encephalitis demonstrate ongoing neurodevelopmental impairments. 7 Long-term sequelae included developmental delay (35%), behavior problems (18%), intellectual impairments (17.6%), and motor deficits (18%).…”
Section: Discussionmentioning
confidence: 99%
“…Survivors of pediatric encephalitis demonstrate long-term neurological sequelae ranging from neurocognitive impairments and related learning challenges to behavioral and personality changes. 64 , 65 , 66 A 2016 meta-analysis found that a nearly half of the children who recover from viral encephalitis demonstrate ongoing neurodevelopmental impairments. 7 Long-term sequelae included developmental delay (35%), behavior problems (18%), intellectual impairments (17.6%), and motor deficits (18%).…”
Section: Discussionmentioning
confidence: 99%
“…Their introduction through an NIHR programme grant in applied research was associated with a reduction in the time to aciclovir treatment for those with HSV encephalitis. The programme examined where delays occur, introduced innovative measures such as a lumbar puncture pack to streamline management [ 15 , 26 ], and included intense efforts to raise awareness of encephalitis and the national guidelines, in conjunction with The Encephalitis Society, our partner in patient and public involvement and engagement [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A UK study showed that the median time to treatment for suspected HSV encephalitis was 48 (range: 2-432) hours (6). Since the publication of the clinical guidelines for the management of suspected encephalitis in 2012, more recent studies have shown a reduced median time to treatment for suspected encephalitis to around 15 hours (7, 8)). But while a number of studies have reported on the favourable (modified Rankin Scale of 0–3) clinical outcomes associated with the early treatment (≤ 48 hours from admission) of HSV encephalitis (915), there is limited research into the potential impact on healthcare resource utilisation and costs.…”
Section: Introductionmentioning
confidence: 99%